Legislatif Kuat, Demokrasi Stabil? - Munadhil Abdul Muqsith (ADALAH, 2020)
Abstract:The concept of people's sovereignty truly lies in the representation of the people's representatives or legislators. The strong legislative control over the executive makes the allocation of natural and human resources well controlled. The power granted by the people to the executive can be limited constitutionally by the legislature. In this article the author wants to discuss the urgency of strengthening the legislature to strengthen a country's democratic system. Without a strong legislature, it is certain that a country's democratic system is weak, and vice versa.Keywords: Legislature, Democracy, State Abstrak:Konsep kedaulatan rakyat sejatinya berada pada representasi perwakilan rakyat atau legislator. Kuatnya kontrol legislatif terhadap eksekutif maka alokasi sumber daya alam dan manusia dapat terkontrol dengan baik. Kekuasaan yang diberikan rakyat kepada eksekutif dapat dibatasi secara konstitusional oleh legislatif. Dalam artikel ini penulis ingin membahas urgensi penguatan legislatif  untuk menguatkan sistem Demokrasi suatu negara. Tanpa adanya legislatif yang kuat, maka dipastikan system demokrasi suatu negara menjadi lemah, begitu pula sebaliknya.Kata Kunci: Legislatif, Demokrasi, Negara